Barriers and challenges private higher education institutions face in the management of quality assurance in South Africa - Stander, E.; Herman, C. (South African Journal of Higher Education, 2017)
With globalisation and the rise of the knowledge economy, there has been a worldwide increase in demand for higher education (HE) which has resulted in the proliferation of private higher education institutions (PHEIs). Subsequently, quality assurance (QA) and the management of the QA processes of these institutions have become increasingly important. QA of PHEIs in South Africa is a contested area. On the one hand, it aims at protecting the public from unscrupulous providers, on the other, the complexity of the QA legislative framework has become a major concern to private providers. This qualitative study focused on the experiences of PHEIs in South Africa in the management of QA, while at the same time complying with QA and accreditation processes. Based on the Octet of Quality in Higher Education, a model adapted from Zaki and Zaki Rashidi (2013); the findings identified three major categories related to the barriers and challenges particular to PHEIs as they engage in the management of QA; namely, resources, such as physical and financial resources; capacity development, such as staff roles and responsibilities, academic leadership and development, and research; and programme design, including curriculum design.